Prenatal diagnosis and postnatal verification in fetuses with total anomalous pulmonary venous connection - Xue, Xiaoying; Wu, Qiumei; Xiong, Mingtao; Ling, Wen; Guo, Shan; Ma, Hong; Huang, Biying; Liu, Min; Qiu, Xiuqing; Weng, Zongjie (Frontiers in Pediatrics, 2023)
Objective: To systematically diagnose Total Anomalous Pulmonary Venous Connection (TAPVC) in fetuses by four-step prenatal ultrasound and verify its accuracy. Pay attention to the classification, pulmonary venous obstruction, and the associated malformations in TAPVC fetuses and follow up on their prognosis. Methods: A total of 62 fetuses with TAPVC who underwent prenatal ultrasonography and were confirmed by postnatal echocardiography, surgery or postabortion anatomy were included in the study. Four-step prenatal ultrasound procedure was used to screen the fetuses suspected to have TAPVC. The sonographic features, clinical data, and prognosis of the fetuses with TAPVC were retrospectively analyzed. Results: Of the 62 TAPVC fetuses, 20 were supracardiac, 12 intracardiac, 21 infracardiac and 9 mixed. 30 cases with RAI were correctly diagnosed, 11 cases with other intracardiac and extracardiac malformations, 1 case was misdiagnosed; 21 cases with isolated TAPVC, 6 cases were missed prenatally, one case was diagnosed as intracardiac type prenatally and proved to be mixed type (intracardiac Type + supracardiac type) by echocardiography after birth. Of the 13 TAPVC live births, 4 infants died in the neonatal period without operation. Of the 9 infants who underwent the operation, 5 recovered well and survived, one patient with superior vena cava obstruction and collateral circulation formation survived, and 3 patients died after the operation. Conclusion: The four-step prenatal ultrasound procedure can comprehensively and systematically evaluate fetal TAPVC, including the classification, the existence of obstruction, and associated malformations, providing more evidence for subsequent prenatal counselling and neonatal assessment after birth. Isolated TAPVC is prone to missed diagnosis.